Adverse childhood experiences: prevalence and associated factors among South African young adults. Issue 12 (December 2019) - Manyema, Mercy; Richter, Linda M.
Abstract: While adverse childhood experiences (ACEs), as described by the CDC-Kaiser Permanente Study, are reportedly common in both high and low-income settings, evidence on the epidemiology of ACEs in low-income settings is scarce. This study aimed to determine the prevalence of ACEs reported in young adulthood and assess their association with childhood maternal, household and community factors. We used data from the 22–23 year wave of the Birth to Twenty Plus (Bt20+) study in South Africa, the largest and longest running birth cohort in Africa. With ACEs as the main outcome measure, their association with childhood factors was assessed using regression models. As demonstrated in high-income settings, ACEs are highly prevalent in this young adult population in a middle income country. Both household and community socio-economic status in childhood was associated with the experience of ACEs and the likelihood of experiencing multiple ACEs. The attenuation of significance in adjusted models suggested that individual ACEs are correlated and may exert their effects through other ACEs. Interventions for the prevention of ACEs need to be directed not only at individuals but households as well as communities. Abstract : Developmental biology; Epidemiology; Public health; Quality of life; Interrelated; Abuse; Clustering; Household dysfunction; ACE score; Adverse childhood experiences; Neglect; Adversity; Early childhood development.